2006
DOI: 10.1089/aid.2006.22.1014
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Unusual Cysteine Variants in gp120 Envelope Proteins from Early HIV Type 1 Infections from a Phase 3 Vaccine Efficacy Trial

Abstract: During the course of a large-scale HIV-1 vaccine field trial (VAX004), full-length gp120 sequences were determined for 349 new HIV-1 infections. The data collected represent the largest survey of full-length gp120 sequences from new HIV-1 infections ever assembled. Previous studies have shown that subtype B viruses typically possess 18 cysteine residues that are covalently linked to form 9 conserved disulfide bridges. However, in this study we found that approximately 20% of the trial participants possessed en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
(40 reference statements)
3
16
0
Order By: Relevance
“…During the analysis, we observed variability in disulfide bonding, particularly in the C1-V1/V2 region of the protein. This variability is consistent with recent reports that have directly [39] or indirectly [40] highlighted that alternative connection of disulfide linkages is possible in a number of recombinant envelope glycoproteins generated from CHO and HEK 293T cells. Concomitant comparative antibody binding analysis using SPR of wild-type gp120 and disulfide-stabilized gp120 (gp120 L1-SS-L2) also confirmed the improved exposure of the CD4i-site on the disulfide-stabilized gp120.…”
Section: Discussionsupporting
confidence: 92%
“…During the analysis, we observed variability in disulfide bonding, particularly in the C1-V1/V2 region of the protein. This variability is consistent with recent reports that have directly [39] or indirectly [40] highlighted that alternative connection of disulfide linkages is possible in a number of recombinant envelope glycoproteins generated from CHO and HEK 293T cells. Concomitant comparative antibody binding analysis using SPR of wild-type gp120 and disulfide-stabilized gp120 (gp120 L1-SS-L2) also confirmed the improved exposure of the CD4i-site on the disulfide-stabilized gp120.…”
Section: Discussionsupporting
confidence: 92%
“…Once effective neutralizing antibodies are present, neutralization-sensitive variants, such as Q655R, would be selected against and rapidly disappear from plasma. The possibility that viruses from early infections may contain mutations resulting in unusual structures is consistent with a previous study (24) which found that viruses recovered from the same clinical cohort as the 108060 virus had an unexpectedly high frequency of mutations that affected the disulfide structure of gp120.…”
Section: Discussionsupporting
confidence: 88%
“…According to the disulfide connectivity in a previously analyzed recombinant, monomeric HIV envelope protein, gp120,2 nine disulfide bonds should be present for each monomeric unit of CON-S gp140 ΔCFI, if the expected disulfide bonding pattern is conserved. This expected disulfide connectivity for the monomeric form of CON-S gp140 ΔCFI is shown in Figure 5A, in which the disulfide bonds define the boundaries of the variable regions (V1–V5) as well as conserved domains in HIV Env protein 2, 39. Since CON-S gp140 ΔCFI is an oligomeric form of Env, we accounted for the possibility that the disulfide bonding pattern could be significantly different.…”
Section: Resultsmentioning
confidence: 98%